A scientists' view of scientometrics: Not everything that counts can be counted - Kenna, R.; Mryglod, O.; Berche, B (Condensed Matter Physics, 2017)
Like it or not, attempts to evaluate and monitor the quality of academic research have become increasingly
prevalent worldwide. Performance reviews range from at the level of individuals, through research groups and
departments, to entire universities. Many of these are informed by, or functions of, simple scientometric indicators and the results of such exercises impact onto careers, funding and prestige. However, there is sometimes
a failure to appreciate that scientometrics are, at best, very blunt instruments and their incorrect usage can be
misleading. Rather than accepting the rise and fall of individuals and institutions on the basis of such imprecise
measures, calls have been made for indicators be regularly scrutinised and for improvements to the evidence
base in this area. It is thus incumbent upon the scientific community, especially the physics, complexity-science
and scientometrics communities, to scrutinise metric indicators. Here, we review recent attempts to do this and
show that some metrics in widespread use cannot be used as reliable indicators research quality. До вподоби це комусь чи нi, але спроби аналiзувати та монiторити якiсть академiчних дослiджень стають все бiльш поширеними у цiлому свiтi. Оцiнювання ефективностi вiдбувається як на iндивiдуальному
рiвнi, так i здiйснюється для наукових груп, факультетiв чи цiлих унiверситетiв. Багато iз таких процедур
напряму залежать або ж беруть до уваги простi наукометричнi iндикатори, а їх висновки можуть впливати на кар’єри, фiнансування та престиж. Проте дуже часто бракує розумiння того, що наукометрики є,
в кращому випадку, досить грубим iнструментом, i їх неправильне використання може привести до неправильних висновкiв. Замiсть того, щоб визнавати пiдйоми чи падiння у рейтингу для iндивiдумiв, вiддiлень чи унiверситетiв на основi таких неiдеальних метрик, робляться заклики до регулярної ретельної
перевiрки iндикаторiв та до покращення доказової бази в цiй дiлянцi. Перевiрка iндикаторiв покладена
на наукову спiльноту, особливо на фiзикiв, експертiв у галузi складних систем та наукометрiї. У цiй роботi
зроблено огляд нещодавнiх спроб показати, що деякi поширенi метрики не можуть слугувати надiйним
iндикатором наукової якостi.